The study of interdisciplinary connections of criminal law and forensic pharmacy in the system turnover of medical drugs - Шаповалов, Валерій Володимирович; Шаповалов, Валентин Валерійович; Шаповалова, Вікторія Олексіївна; Омельченко, Володимир Олександрович (Theory and practice of jurisprudence, 2017)
Everyday activities pharmacist associated with the organization turnover of medical drugs of different pharmacological clinical, legal classification and nomenclature legal groups in health care. However, forensic pharmaceutical practice registers cases of illegal turnover of prohibited substance in Ukraine (pervityn, amphetamine, metkatinon, katinon et al.) by artisanal manufacture of drugs. Activities of pharmacists in the chain of relations «doctor-patient-pharmacist» associated with ongoing responsibility for organizing the turnover of medical drugs in health facilities. Improvement of legal turnover of medical drugs in Ukraine touches on criminal law, administrative and disciplinary experts in the pharmacy dispensing medicines. Irrational use of drugs may be associated with the development of conditions depending on the medication (drug, alcohol dependence, etc.). Also illegal drugs in turnover can be used for criminal purposes or to modify banned in Ukraine drugs or psychotropic substances. The study above mentioned problems is in the plane of interdisciplinary causal relationships between the pharmaceutical, medical and legal sciences. To conduct the study interdisciplinary connections the application of criminal law in the system of forensic pharmaceutical research turnover of medical drugs in health facilities. The impact on the formation of the criminal law are: the doctrine of criminal law; investigative and judicial practice; forensic pharmaceutical, forensic medical, forensic neurological, forensic psychiatric and forensic practice; the supreme court of Ukraine on the unequal application by courts of cassation of the same law of Ukraine on criminal liability in respect of such socially dangerous acts. Detection system intersectional and interdisciplinary connections between criminal law and pharmaceutical disciplines (forensic pharmacy, medicine technology, organization of pharmacy), formulation of theoretical generalizations, eliminate contradictory standards within the same field of law, etc. – should be the priorities of modern jurisprudence that promote the objectives of improving the efficiency of enforcement. Authors studied interdisciplinary connections criminal law, forensic pharmacy and responsibilities specialists of pharmacy and medicine in the implementation of medical drugs in health facilities. Based on forensic pharmaceutical practice proved that infringement of medicine and pharmacy specialist’s procedure turnover of medical drugs has causal relationship with the deterioration of the life and health of patients. The study of pharmaceutical and medicine law will increase the level of legal culture and legal awareness in the chain relationship «doctor-patient-pharmacist» in the turnover of medical drugs.